A PROSPECTIVE OBSERVATIONAL STUDY ON SAFETY AND EFFICACY OF HYDROXYCHLOROQUINE AGAINST DICLOFENAC IN OSTEOARTHRITIS - D, Praveen; T, Rujaswini,; K, Elancheziyan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main aim of this study is to compare the effectiveness of treatment of osteoarthritis (OA) with hydroxychloroquine against diclofenac and to compare the safety of the treatment of OA with hydroxychloroquine against diclofenac. The secondary objectives are the comparison of onset and duration of action of both the treatments. Methods: A prospective interventional study has been done in a tertiary care teaching hospital for 1 year from January 2016 to December 2016. The interventional model included an active control (diclofenac - nonsteroidal anti-inflammatory drugs). The control group received diclofenac 75 mg for 12 weeks, whereas the test group received hydroxychloroquine 200 mg for 3 months. Results: Pain control is significantly rapid in diclofenac group, whereas the duration of action is significantly increased in hydroxychloroquine. It can be clearly seen that the hydroxychloroquine group significantly increases the quality of life when compared to diclofenac group. It is clearly seen that the incidence of gastric ulcers is more common in diclofenac group when compared to hydroxychloroquine group. Conclusion: Hydroxychloroquine offers a newer spectrum in the management of OA. Although it is slow acting, it has significantly increased the quality of patient as it can have a prolonged action. Hence, hydroxychloroquine can be used as a newer entity in the management of OA.